2008
DOI: 10.1073/pnas.0712365105
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of mechanisms of Chinese medicinal formula Realgar- Indigo naturalis as an effective treatment for promyelocytic leukemia

Abstract: To enhance therapeutic efficacy and reduce adverse effects, practitioners of traditional Chinese medicine (TCM) prescribe a combination of plant species/minerals, called formulae, based on clinical experience. Nearly 100,000 formulae have been recorded, but the working mechanisms of most remain unknown. In trying to address the possible beneficial effects of formulae with current biomedical approaches, we use Realgar-Indigo naturalis formula (RIF), which has been proven to be very effective in treating human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
455
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 687 publications
(467 citation statements)
references
References 27 publications
(24 reference statements)
4
455
0
1
Order By: Relevance
“…As a control for siRNA, a corresponding random siRNA sequence (control siRNA: TTC TCC GAA CGT GTC ACG T) was used, lentiviral vector production and construction of stable silenced cells was made by Genechem biology company. 16 We used one representative lung cancer cell lines, H1299. We selected infectants with gynemycin for 72 h and then determined the Pin1 protein levels by immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As a control for siRNA, a corresponding random siRNA sequence (control siRNA: TTC TCC GAA CGT GTC ACG T) was used, lentiviral vector production and construction of stable silenced cells was made by Genechem biology company. 16 We used one representative lung cancer cell lines, H1299. We selected infectants with gynemycin for 72 h and then determined the Pin1 protein levels by immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These are highly bioactive. For example, tanshinone IIA exerts vasorelaxative activity, has antiarrhythmic effects, provides protection against ischemia reperfusion injury Gao et al, 2008;Sun et al, 2008), and exhibits anticancer activities (Efferth et al, 2008;Lee et al, 2008;Wang et al, 2008;Gong et al, 2011). In addition, tanshinones have been reported to have a broad spectrum of antimicrobial activities against various plant pathogens, including rice (Oryza sativa) blast fungus Magnaporthe oryzae (Zhao et al, 2011).…”
mentioning
confidence: 99%
“…Wang et al (27) reported that RIF, when used in a murine APL model, promoted ubiquitination and degradation of the PML/RARα oncoprotein by inducing expression and transportation of aquaglyceroporin-9 which degraded PML/RARα. It also enhanced G1/G0 arrest of APL cells by regulating multiple targets of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%